Has Russia an environmental policy? The case of the Tomsk regional ecological committee - Judith Marquand (Economic and Environmental Studies (E&ES), 2013)
The article deals with the issue of environmental policy and its implementation in Russia on the example of the Tomsk Region for the period 1989-2000. The author discusses the state of the environment, institutional arrangements and legal position in the 1990s, how the Tomsk Regional Ecological Committee (TREC) actually carried out its responsibilities in the mid-1990s, what Putin did to the Ecological Committees, and where TREC stood at the end of 2005.
Keywords: 330; environmental policy; Russia; Omsk